Interpreting TKA Math Results: Analytic Framework for Elementary Students’ Ability and Readiness Distribution - Nur Khikmah (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2026)
This study aimed to describe elementary students’ mathematics achievement based on the Mathematics Academic Ability Test (Tes Kemampuan Akademik/TKA) tryout, analyze the distribution of their achievement levels, and evaluate their readiness for future mathematics assessments. A quantitative descriptive research design was employed involving 28 sixth-grade students at SD Negeri Banyumanik 01 Semarang, Indonesia. Data was obtained from a mathematics TKA tryout consisting of 30 items administered in April 2026. The data were analyzed using descriptive statistical techniques, including the calculation of mean, minimum and maximum scores, frequency distributions, percentage distributions, and achievement-level classifications. The results revealed that the students obtained an average score of 58.45, with scores ranging from 36.67 to 90.00. Based on the achievement-level classification, 14.29% of students were categorized as high achievers, 17.86% as fair achievers, 21.43% as moderate achievers, 25.00% as low achievers, and 21.43% as very low achievers. Overall, 46.43% of students were classified in the low and very low achievement categories, indicating that a substantial proportion of students still experienced difficulties in mastering mathematical concepts and problem-solving skills. Although all students completed the assessment, considerable variation in score accuracy was observed. These findings suggest that students’ readiness for future mathematics assessments remains at a moderate level. The study highlights the importance of utilizing TKA tryout results as diagnostic data for designing remedial, enrichment, and differentiated instructional strategies to improve students’ mathematical understanding and academic performance.